FT-IR Characterization and Phylogenetic Analysis of Patchouli Oil from West Aceh and Aceh Jaya using PCA and HCA - Nisak, Khairun; nariska, Sandiana; Suhud, Khairi; Sufriadi, Elly (Journal of Carbazon, 2024)
This study aims to characterize and compare the chemical composition of patchouli oil from various regions in Aceh, Indonesia, using Fourier-transform Infrared Spectroscopy (FT-IR) combined with Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA). Patchouli oil samples from five distinct locations within West Aceh and Aceh Jaya Regencies were analyzed, focusing on the 1800-500 cm range. The FT-IR spectra revealed significant chemical markers, with notable absorption bands corresponding to aliphatic C-H, C=O, and C=C stretching vibrations. Multivariate analyses showed distinct clustering patterns, with four samples (POSM, POSP, POT, and POW) exhibiting high chemical similarity and clustering together, while one sample (POP) formed a separate cluster, indicating a lower degree of similarity. PCA analysis of the original spectra in the 1800-500 cm range yielded a cumulative PC1 and PC2 value of 89%. The HCA dendrogram highlighted a significant relative distance of 10 between the POP sample and the other four samples, indicating minimal relatedness, with the closest relatedness observed between POSM and POSP, having a relative distance of 1.1. This study demonstrates the effectiveness of FT-IR spectroscopy combined with PCA and HCA in distinguishing chemical profiles of patchouli oil from different regions, providing insights into geographical and varietal influences on oil composition. The findings are crucial for quality control and standardization in the patchouli oil industry, with further molecular studies recommended to corroborate and enhance understanding of genetic diversity among patchouli varieties in Aceh.